25.3k views
3 votes
Solve for x.

5x + 3 = 2(x + 3) + 3x – 6

2 Answers

3 votes

Answer:

No solution

Step-by-step explanation:Does that make sense to u, You distribute 2 with x and 3 which gets you 2x+6. Combine like terms and you will get 5x on the right side, since the 6's cancel out. 5x+3=5x.

X cancels out and u are left with 3=nothing which makes it no solution

Solve for x. 5x + 3 = 2(x + 3) + 3x – 6-example-1
User JYoThI
by
4.9k points
2 votes

9514 1404 393

Answer:

no solution

Explanation:

We can eliminate parentheses and collect terms.

5x +3 = 2x +6 +3x -6

5x +3 = 5x

3 = 0 . . . . . . . . subtract 5x from both sides

There is no value of x that will make this true. There is no solution.

User EdWood
by
4.6k points